Polysulfone mixed matrix membranes with biosynthesis nanoparticles: enhancement of interface compatibility and antibacterial membrane seperation process - Yusof, Khairul Nazri (2020)
This study investigates the effect of biosynthesis silver nanoparticles (bio-AgNPs) structure towards PSf membranes performance. The addition of bio-AgNPs in the membrane formulation was aimed to improve antibacterial properties and interface compatibility of the polymer mixed matric membrane. In this work, facile green synthesis method of silver nanoparticles was prepared using Parkia speciosa (Petai) leaves extract silver nitrate aqueous solution. The bio-AgNPs/PSf membranes was fabricated using phase-inversion process. Characterization of the synthesized bioAgNPs and mixed matrix membranes via UV-Vis spectroscopy (UV-Vis), Field emission scanning electron microscope (FESEM), Transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). Surface plasmon resonance for bio-AgNPs was assigned at 465 nm with brown colour. FTIR spectroscopy identified the biomolecules capped on the surface of nanoparticles are phenol, flavonoid and terpenoid compounds. The microstructure and structural analyses had shown that AgNPs possessed good characteristics with spherical shapes, small average size of particles (59.96 nm), and small crystallite size. The bio-AgNPs also showed significant potential antibacterial activity against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). The addition of bio-AgNPs was able to enhance the hydrophilicity of composite PSf membranes which proved by decreasing the value of contact angle. Meanwhile, structure on bottom layer shown a porous bulk with finger-like structure and macroviod structure which is responsible for mechanical support. Finger-like structure on top layer became smaller with increment of bio-AgNPs because of its hydrophilicity properties. Hence, the pure water flux also will increase because the hydrophilicity properties was an essential factor for water permeability. The molecular interaction between molecules was investigated using Dynamic mechanical analysis (DMA) and silver leaching analysis by Inductive coupled plasma mass spectrometer (ICP-MS). vi As revealed, the strength of molecular interaction between AgNPs and PSf molecules was improved with addition of bio-AgNPs. Hence, overall the results showed that the incorporation of bio-AgNPs able to improve antibacterial properties and interface compatibility of the polymer mixed matric membrane